2017
DOI: 10.1039/c7nr01841j
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid nano- and microchamber arrays for encapsulation of small hydrophilic molecules featuring drug release via high intensity focused ultrasound

Abstract: Long term encapsulation combined with spatiotemporal release for a precisely defined quantity of small hydrophilic molecules on demand remains a challenge in various fields ranging from medical drug delivery, controlled release of catalysts to industrial anti-corrosion systems. Free-standing individually sealed polylactic acid (PLA) nano- and microchamber arrays were produced by one-step dip-coating a PDMS stamp into PLA solution for 5 s followed by drying under ambient conditions. The wall thickness of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Micelles were tailored by controlling the ratio of hydrophilic and hydrophobic block copolymers and exhibited a significant release of dexamethasone. Gai et al developed free-standing biocompatible polylactic acid (PLA) nano- and micro-chamber arrays using two different methods for encapsulation, one-step dip-coating and microcontact printing of air, NaCl, and rhodamine B dye [26]. This work showed that the formation of microchambers can provide long-term encapsulation of small hydrophilic molecules and the release profiles of the microchambers with and without the use of HIFU [26].…”
Section: Physical Stimuli-responsive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micelles were tailored by controlling the ratio of hydrophilic and hydrophobic block copolymers and exhibited a significant release of dexamethasone. Gai et al developed free-standing biocompatible polylactic acid (PLA) nano- and micro-chamber arrays using two different methods for encapsulation, one-step dip-coating and microcontact printing of air, NaCl, and rhodamine B dye [26]. This work showed that the formation of microchambers can provide long-term encapsulation of small hydrophilic molecules and the release profiles of the microchambers with and without the use of HIFU [26].…”
Section: Physical Stimuli-responsive Systemsmentioning
confidence: 99%
“…Gai et al developed free-standing biocompatible polylactic acid (PLA) nano- and micro-chamber arrays using two different methods for encapsulation, one-step dip-coating and microcontact printing of air, NaCl, and rhodamine B dye [26]. This work showed that the formation of microchambers can provide long-term encapsulation of small hydrophilic molecules and the release profiles of the microchambers with and without the use of HIFU [26]. With the use of HIFU treatment, the microchambers release around four times the amount of the group without the HIFU treatment [26].…”
Section: Physical Stimuli-responsive Systemsmentioning
confidence: 99%
“…Gai et al, also used trapped air inside the microwells for the on-demand release of encapsulated drugs 230. They first prepared microwells on PDMS membranes and loaded the wells with a model compound; Rhodamine B.…”
Section: Acoustically Active Materials For Fus Theranosticsmentioning
confidence: 99%
“…Enhanced mechanical properties of PEGOM films could be specifically advantageous for making 3D structures, e.g., an array of microchambers developed recently . Potential applications of these structures include micropackaging of drugs, or sensors for rapid diagnostics of biological fluids, where resilience of the microchambers toward external stresses is required to avoid accidental burst release, the event that could be catastrophic. Moreover, GO could be used to provide near infrared (NIR) light responsiveness, which is important for many release‐on‐demand applications in biological systems as NIR light penetrates into the biological tissues for up to 10 cm causing no harm …”
Section: Introductionmentioning
confidence: 99%